LEGAL CONSIDERATIONS FOR THE USE OF TECHNOLOGY IN THE DIGITAL BANKING SECTOR - Suryadarma, Fatika Redita (Ridwan Institute, 2024)
With the rapid development of the digital economy in Indonesia, the development of digital banking has a great opportunity to grow. The potential to meet customer needs and expectations for faster and more efficient banking services based on digital technology has made the image of digital banks more popular among the public, especially for young people. This study explores the effectiveness and completeness of regulations governing the use of technology in Indonesia's rapidly transforming digital banking sector, which is currently undergoing a transformation process. By evaluating the current regulatory framework, the study provides insights into potential gaps and areas where the regulations may need to be strengthened or updated to ensure the secure and efficient operation of digital bank services. The use of artificial intelligence (AI) in the banking sector contributes to the transformation to digital banking, especially in identifying fraudulent attempts, assisting in the process of surveillance, analysis, and evaluation of transactions, as well as improving the standards of credit scoring, customer service, and automation. This article provides an overview of considerations if Indonesia implements international standard regulations for the security of cyber systems for the smooth running of digitalbank services. This paper emphasizes the need to implement a collaboration-based approach by involving government, industry, academia, and civil society to strengthen global digital resilience and security. The application of DORA principles in Indonesia can help strengthen the digital infrastructure of banks in the country.